Implementasi Pendidikan Karakter: Integrasi Lagu Melayu Sambas dalam Pembelajaran pada MIN Kabupaten Sambas - Purniadi Adi Putra (Lembaga penelitian dan pengabdian kepada Masyarakat, 2019)
The lack of understanding and knowledge of children about the song and the type of song itself will have an impact on the character crisis, this is due to many who memorize the western-style romance songs compared to their own folk songs. The aim of learning Sambas Malay regional songs in the madrasa introduces directly to students and preserving Sambas Malay local culture especially at the elementary level children will sustain in the process of maintaining regional culture to stay alive, transfer and develop by means of learning processes contained in subjects and extracurricular regional art has implications for student character education. This study uses descriptive qualitative methods. The focus of this research is art teachers, students and madrasah principals with data sources from the MIN Sambas District of the Sambas Malay ethnic group. The results of this study are to strengthen the values of Sambas Malay character as a basic foundation in maintaining local wisdom, song art education as the basis of education in shaping the soul and personality of noble character (akhlakul karimah), the meaning of Sambas tandak song has religious value, bellale song ' having social values in collaboration, Sambas river songs flooded with environmental values, mak jage's rock songs having the value of peaceful love characters, and Allo 'Galing songs having social values and cooperation.